Audit Attributes, Ownership Structures, and Financial Reporting Timeliness: Evidence from Nigeria’s Oil and Gas Sector - GBADEBO, Adedeji Daniel (Journal of Financial and Behavioural Accounting, 2025)
This study investigates the relationship between audit attributes and the financial reporting timeliness of listed oil and gas firms in Nigeria, while examining the moderating role of government ownership. Drawing on agency theory, political cost theory, and resource dependence perspectives, the research employed panel data analysis covering a ten-year period. The study utilized data from 12 listed oil and gas firms on the Nigerian Exchange Group (NGX) between 2013 and 2022, yielding 120 firm-year observations. Secondary data were extracted from annual reports and audited financial statements. Both fixed-effects and random-effects estimators were initially estimated, with the Hausman test guiding the selection of the fixed-effects model as the preferred specification. To ensure robustness, feasible generalized least squares (FGLS) and panel-corrected standard errors (PCSE) estimations were also employed. The findings reveal that audit firm size significantly improves reporting timeliness, whereas audit fee and tenure show no direct influence. Furthermore, government ownership exerts a moderating effect, strengthening the influence of audit fee and tenure on reporting timeliness but reducing the efficiency advantages associated with larger audit firms. These results highlight the interplay between institutional ownership structures and audit characteristics in shaping disclosure practices within an emerging market context. The study contributes to literature on financial reporting quality and corporate governance, offering insights for regulators, policymakers, and practitioners seeking to enhance transparency, accountability, and investor confidence in Nigeria’s strategic oil and gas sector.